Implementation of SintromacWeb®, a new internet-based tool for oral anticoagulation therapy telecontrol: Study on system consistency and patient satisfaction - Ferrando, Fernando; Mira, Yolanda; Contreras, María Teresa; Aguado, Cristina; Aznar, José Antonio (Thrombosis and Haemostasis, 2010)
Most computer- or internet-assisted systems for oral anticoagulation therapy (OAT) telemanagement have limitations when it comes to implementation within a healthcare center. It was the objective of this study to evaluate convenience and patient satisfaction with the use of SintromacWeb→, a new OAT telecontrol system, compared with the conventional control. SintromacWeb® consists of a point-of-care device for patient international normalized ratio (INR) self-testing and software that allows internet mediated interaction with physicians. Patients initiated the use of SintromacWeb→ and were followed up during a three-month period. A score-based questionnaire was completed in three controlled visits, and data were subsequently analysed. A total of 102 patients were enrolled. At first visit, 55.7% of the patients had their INR within normal range, and 64.9% at the final visit. Internal consistency of the questionnaire was good (Cronbach‘s α: 0.79). Scores in the questionnaire were independent of patient’s age, education level, working status and INR value. The most valued features of SintromacWeb® were: fewer visits to the hospital, simplicity and convenience of the system, and time administration for control tasks (86.7%, 82.7% and 77.6% of very satisfied patients, respectively). Also, patients showed indifference or were dissatisfied with the conventional system. At the final visit, 99% of patients declared that they were satisfied with their OAT control. Moreover, all patients continued using Sintrom -acWeb→ after completion of the study. In conclusion, SintromacWeb→ telecontrol is a new model for management of anticoagulated patients. It was highly accepted and can be used by all patients regardless of their sociodemographic characteristics.
Keywords: Oral anticoagulation therapy; SintromacWeb; telecontrol; internet